Pengaruh Peer Support terhadap Career Decision Self Efficacy pada Mahasiswa Tingkat Akhir - Farhany Luthfiana Salahudin; Sartika, Dewi; Muhamad Arif Saefudin (Bandung Conference Series: Psychology Science, 2024)
Abstract. The study aims to test how much Peer Support influences self-efficacy in career decision-making in graduate students in Bandung Raya. Peer support is defined as the process of obtaining career-related information and advice, emotional support, and guidance from peers. CDSE is the level of confidence that an individual has in his ability to complete career related tasks measured through five skills: self appraisal, gathering occupational information, goal selection, making plans, and problem solving. The approach used in this study is quantitative non-experimental with cross-sectional research design performed on a total of 326 subjects. Sampling methods are non probability sampling and convenience samplings. The results of this study show that Peer Support has a positive influence on career decisions self efficacy, which is demonstrated by p value 0.00 and beta value of 0.970. The Peer Support scale research measurement was adapted by Salim et al based on the Zhang & Huang theory. Career Decision Self Efficacy was adopted by Sawitri based on Taylor & Betz theory, and the results showed that peer support had an influence on career decision self-efficacy of 44.9% and 55.1% was influenced by other variables. Abstrak. Penelitian ini memiliki tujuan untuk menguji seberapa besar pengaruh Peer Support terhadap Career Decision Self Efficacy pada Mahasiswa Tingkat akhir di Bandung Raya. Peer Support didefinisikan sebagai proses mendapatkan informasi dan nasihat yang berkaitan dengan karir , dukungan emosi, dan panutan dari teman sebaya. Sedangkan, CDSE didefinisikan sebagai tingkat keyakinan yang dimiliki individu tentang kemampuannya menyelesaikan tugas terkait karir yang diukur melalui lima kemampuan yaitu, self appraisal, gathering occupational information, goal selection, making plans, dan problem solving. Pendekatan yang dilakukan dalam penelitian ini yaitu kuantitatif non eksperimen dengan desain penelitian cross-sectional yang dilakukan pada Subjek penelitian sebanyak 326. Metode pengambilan sampel yaitu non probability sampling tengan Teknik convenience sampling. Hasil dari penelitian ini terlihat bahwa Peer Support memiliki pengaruh positif pada career decisions self efficacy, yang ditunjukan oleh p value 0.00 dan nilai beta sebesar 0.970. Alat ukur penelitian skala Peer Support diadaptasi oleh Salim et al berdasarkan teori Zhang & Huang. Career Decision Self Efficacy didaptasi oleh Sawitri berdasarkan teori Taylor & Betz. Hasil menunjukkan Peer Support berpengaruh pada Career Decision Self Efficacy sebesar 44.9% dan 55.1% dipengaruhi oleh variabel lainnya.